Determinants of ShopeePay Usage Intention Among Generation Z in Malang: A TAM-Based Analysis - Pinem, Nia Rifani; Sumantri, Vietha Devia Sagita (KINERJA, 2025)
E-wallets are a transaction tool that is most in demand by the people of Indonesia. One of the e-wallets that has a high number of enthusiasts in Indonesia is ShopeePay. This study aims to determine the factors influencing interest in using the ShopeePay e-wallet as a transaction tool for Generation Z in Malang. This study uses the TAM (Technology Acceptance Model) model with independent variables of perceived usefulness, perceived ease of use, perceived risk, perceived security, trust, and the dependent variable, namely interest in use. This research is quantitative. This research uses a purposive sampling method with data analysis using Partial Least Squares (PLS). The criteria in this study are members of Generation Z, born between 1997 and 2007, who use the ShopeePay e-wallet. The total number of respondents is 100 individuals. The results showed that perceived usefulness, perceived ease of use, and trust affect the interest in using the ShopeePay e-wallet. Meanwhile, perceived risk and perceived security do not affect interest in using the ShopeePay e-wallet.